Manajemen Pembelajaran Guru pada Madrasah Ibtidayah Negeri Dalam Meningkatkan Lulusan Mutu Berkualitas di Kabupaten Bireuen: Penelitian - Murhadi; Marwan; Munawar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the learning management of teachers at Madrasah Ibtidaiyah Negeri in Bireuen Regency in improving graduate quality. A descriptive qualitative method was applied, using observation, interviews, and documentation. The results revealed that learning planning was based on initial student assessments, character-based and Islamic values-integrated modules, and contextual methods. Organization involved student grouping, flexible class arrangements, and varied learning media. Implementation was interactive, integrative, and participatory. Supervision was conducted through structured classroom observations, document evaluations, and reflective discussions. Effective learning management had a positive impact on the quality of madrasah graduates.